The effect of human capital, structural capital, customer capital, managerial ownership, and leverage toward profitability of company - Tia Maharani; Khoirul Fuad (Journal of Advanced Multidisciplinary Research, 2020)
Profitability is the ability of a company to generate profits. In an effort to achieve profitability, companies must be able to convert and be able to combine the necessary resources effectively and efficiently. These efforts can help in increasing profits earned by the company. One of the factors that can determine the good or bad performance of a company is profit, because of profit The purpose of this study is to study and analyze the influence of Human Resources, Structural Capital, Customer Capital, Good Governance and influence on Company Profitability. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2017. The samples obtained by purposive sampling technique, obtained a sample of 38 companies. The technique of taking data. To get secondary data from IDX. The results of research using multiple regression analysis are: Human resources have no significant negative effect on profitability. Structural capital has a significant positive effect on profitability. Customer capital has a significant positive effect on profitability. Ownership is negative about profitability. Leverage has a significant negative effect on profitability.